A comparison of spectral unmixing to conventional compensation for the calculation of fluorochrome abundances from flow cytometric data. Issue 11 (15th July 2022) - Novo, David
Abstract: Traditionally, flow cytometers acquired data using the same number of detectors as fluorochromes being measured in the experiment. More recently, spectral flow cytometers utilize a larger number of detectors than fluorochromes. This seemingly small difference opens the door to a wide variety of mathematical tools for the calculation of the true fluorochrome abundances from the raw detector values as compared with traditional compensation. This review will provide a brief overview of the mathematics and theory underlying traditional compensation and unmixing focusing on the differences between them and the additional information provided by unmixing approaches.